Novel Antimicrobial Peptides Produced by Candida Intermedia lamap1790 Active Against the Wine-Spoilage Yeast Brettanomyces Bruxellensis - Ganga-Munoz, M; Peña-Bernales, R (Springer Netherlands, 2019)
Brettanomyces bruxellensis negatively impacts on the sensorial quality of wine by producing phenolic compounds associated with unpleasant odors. Thus, the control of this spoilage yeast is a critical factor during the winemaking process. A recent approach used to biocontrol undesired microorganisms is the use of yeast released antimicrobial peptides (AMPs), but this strategy has been poorly applied to wine-related microorganisms. The aim of this study was to evaluate the antifungal capacity of Candida intermedia LAMAP1790 against wine-spoilage strains of B. bruxellensis and fermentative strains of Saccharomyces cerevisiae, and also to determine the chemical nature of the compound. The exposure of strains to the supernatant of C. intermedia saturated cultures showed antifungal activity against B. bruxellensis, without affecting the growth of S. cerevisiae. By fractionation and concentration of C. intermedia supernatants, it was determined that the antifungal activity was related to the presence of heat-labile peptides with molecular masses under 5 kDa. To our knowledge, this is the first report of AMPs secreted by C. intermedia that control B. bruxellensis. This could lead to the development of new biocontrol strategies against this wine-spoilage yeast. © 2018, Springer Nature Switzerland AG.